Rotating detonation mode recognition using non-intrusive vibration sensing. (15th May 2020) - Zhong, Yepan; Wu, Yun; Jin, Di; Yang, Xingkui; Chen, Xin
Abstract: Rotating detonation engine can be integrated with gas turbines to realize a high-performance power unit. We propose a novel method of non-intrusive vibration sensing for rotating detonation mode recognition. The conventional method is intrusive and exposes the pressure sensor to the high-temperature and high-pressure detonation wave, which limits the sensor life. In the proposed method, the vibration sensor is installed on the outer wall of the combustor, thus ensuring its safety and longevity. A comparison of the vibration sensing results at two installation sites shows that the vibration sensor must be installed on the propagation path of the detonation wave and downstream of the pre-detonator. In rotating detonation of hydrogen-air mixture, vibration sensing can recognize three rotating detonation modes, namely, stable, unstable, and failure. The frequency spectrum of vibration is consistent with that of pressure, and the discontinuities in the unstable case can be recognized in the time-frequency spectrum. The calculated phase difference between vibration and pressure agrees well with the actual installation angle. The phase space patterns and distributions of wavelet entropy are found to differ in the three rotating detonation modes. Vibration sensing is demonstrated to be a potential non-intrusive method for the mode recognition of a rotating detonation wave. Highlights: Rotating detonation mode recognition by vibration sensing. Vibration signal features of rotating detonation. The relationship between vibration and pressure of a detonation wave.